Familial Multiple Lipomatosis: Report of Two Cases - Imercı, Ahmet; Kaya, Ahmet; Ilyas, Gokhan; Surer, Levent (Fırat University, 2012)
Familial multiple lipomatosis (FML) occurring in an individual without apparent cause may be a separate disease entity or it may be a manifestation of the familial form where the family is too small to show other affected members. In this study we presented the cases of two operated brothers with FML. They were aged 61 and 47, had swelling and pain on arms, body and thigh, and difficulty in dressing. Clinical features, genetic evidence and treatment options are reviewed.

Belirgin bir neden olmadan bir bireyde meydana gelen Ailesel Multipl Lipomatozis (AML), ayrı bir hastalık antitesi olabilir veya ailenin etkilenen diğer üyelerin görülemeyecek kadar küçük olduğu durumlarda ailesel formun bir belirtisi olabilir. Çalışmamızda AML nedeniyle opere edilen iki erkek kardeşi sunmayı amaçladık. Yaşları 61 ve 47 olan hastaların kollarda, gövdede ve uylukta şişlik, ağrı ve elbise giymekte zorluk şikayeti mevcuttu. Hastalığın klinik özellikleri, genetik bulguları ve tedavi seçenekleri tartışıldı.
Ailesel Multipl Lipomatosis: İki Olgu Sunumu